KAJIAN TEOLOGIS DAMPAK COVID 19 TERHADAP PERILAKU ANAK DI KELUARGA KRISTIANI - Theodora Desy Natalia Harli Martono; Singgih Prastawa (CV. ADIBA AISHA AMIRA, 2024)
Learning motivation plays a crucial role in all aspects of education. Therefore, this research aims to determine the impact of understanding the Word of God on students' learning motivation within the context of a Theological College. The Word of God holds a key role in cultivating students' learning motivation, as it is understood as the voice of God. The Word of God is also used for educating in truth, rebuking, and improving the lives of every individual. The objectives of this study are to understand the influence of understanding the Word of God on learning motivation, to determine the significance between learning motivation and student achievement in the Theological College environment, and to explore the influence of students' understanding of the Word of God on the improvement of learning quality within the Theological College. This research utilizes a qualitative method with a literature review approach. The method not only mentions the research itself but also includes the subjects/objects and analysis. The study results indicate that students who rely on the Word of God will experience an impact on their learning motivation and achievement. Therefore, to enhance the quality of Theological students' learning motivation, students must have a good ability to rely on the Word of God to create a compelling and optimal learning atmosphere, thus improving the quality of education in the Theological College.